The impact of point defects in n-type GaN layers on thermal decomposition of InGaN/GaN QWs - Mikolaj Grabowski (Nature Portfolio, 2021)
Abstract The aim of this paper is to give an experimental evidence that point defects (most probably gallium vacancies) induce decomposition of InGaN quantum wells (QWs) at high temperatures. In the experiment performed, we implanted GaN:Si/sapphire substrates with helium ions in order to introduce a high density of point defects. Then, we grew InGaN QWs on such substrates at temperature of 730 °C, what caused elimination of most (but not all) of the implantation-induced point defects expanding the crystal lattice. The InGaN QWs were almost identical to those grown on unimplanted GaN substrates. In the next step of the experiment, we annealed samples grown on unimplanted and implanted GaN at temperatures of 900 °C, 920 °C and 940 °C for half an hour. The samples were examined using Photoluminescence, X-ray Diffraction and Transmission Electron Microscopy. We found out that the decomposition of InGaN QWs started at lower temperatures for the samples grown on the implanted GaN substrates what provides a strong experimental support that point defects play important role in InGaN decomposition at high temperatures.